The Influence of Learning Styles toward Learning Outcomes at the Second Grade Students of Senior High School - Fairus Suryani Munir (Fakultas Tarbiyah dan Ilmu Keguruan, 2022)
There are many students not be able to recognize their individual learning styles so that they are less interested in absorbing the teaching materials that have been provided, and can affect their study English results. This research is aimed at finding out: (1) the students’ Learning Styles (2) the influence of Learning Styles toward Learning Outcomes. Related to the aims of the research, Ex-Post Facto method was carried out. The Population was the second grade students of MAN 2 Parepare in academic year 2019-2020. XI IA1 and XI IA3 were taken as the sample which consists of 37 students. The instruments for collecting data were questionnaire and test. The data obtained were analyzed quantitatively by using Descriptive Analysis and Multiple Linear Regression. Based on the result of the Descriptive Analysis shows that (a) the dominance Learning Style of students is Visual Style with the frequency 18 student (49%) in High Category. (b) Learning Outcomes of students the most dominance is Low category with frequency 19 students (52%). Result analysis of Multiple Linear Regression shows that there is Significant Influence of Visual, Auditory, and Kinesthetic toward Learning Outcomes. It is proved by the data that F-test value is higher than F-table value (11.51 > 2.89). The coefficient of determination that has been adjusted (Adjusted R Square) is 46.7, which means Learning Outcomes as Dependent Variable explained by the Learning Styles as Independent Variable is 51.1%. While 48.9 % is explained by variables outside the variables that used in this research.